.5x-3=.66(x-1)

Simple and best practice solution for .5x-3=.66(x-1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for .5x-3=.66(x-1) equation:


Simplifying
0.5x + -3 = 0.66(x + -1)

Reorder the terms:
-3 + 0.5x = 0.66(x + -1)

Reorder the terms:
-3 + 0.5x = 0.66(-1 + x)
-3 + 0.5x = (-1 * 0.66 + x * 0.66)
-3 + 0.5x = (-0.66 + 0.66x)

Solving
-3 + 0.5x = -0.66 + 0.66x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-0.66x' to each side of the equation.
-3 + 0.5x + -0.66x = -0.66 + 0.66x + -0.66x

Combine like terms: 0.5x + -0.66x = -0.16x
-3 + -0.16x = -0.66 + 0.66x + -0.66x

Combine like terms: 0.66x + -0.66x = 0.00
-3 + -0.16x = -0.66 + 0.00
-3 + -0.16x = -0.66

Add '3' to each side of the equation.
-3 + 3 + -0.16x = -0.66 + 3

Combine like terms: -3 + 3 = 0
0 + -0.16x = -0.66 + 3
-0.16x = -0.66 + 3

Combine like terms: -0.66 + 3 = 2.34
-0.16x = 2.34

Divide each side by '-0.16'.
x = -14.625

Simplifying
x = -14.625

See similar equations:

| 4p=-32 | | (7/11)y=35 | | -7(3b+4)+(22b-1)=0 | | 1.1q-2.4-2.4q=-2.3q-4.3 | | (-6/17)x=20 | | 35x+25y=2275 | | u^2-4u+2=0 | | 8/11=x/9 | | 2x+5+8x=17 | | 2(0-4)=3(0)-8 | | 8ax-3=2x | | 8X2(85-97.4)/3 | | 25/256+1/4 | | 5x^2-3x=-5 | | 4y+9=-3(1-2y)5 | | 4.7(f-0.5)=6(1.6f-8.3f) | | v=25+32t | | 20+4x/7=4 | | W-36=161 | | 3u-2=-8 | | 10x+5y=875 | | 4n+8=9n+8 | | 3x^2=4x+10 | | 7x+5=9x-1 | | 2x^2-125=625 | | 5x+2x=80 | | 5+2x=80 | | 45=x-9x | | 2.7x-4.2=5.7-4.8x | | 2.7x-4.2=5.7-4.8 | | 10x^2=17 | | 3u*7w=x |

Equations solver categories